Employee assessment system for Sunchirin Industry (Malaysia) Berhad / Azniza Md Aziz - Md Aziz, Azniza (2006)
Employee Assessment System was specially designed for Sunchirin Industry (Malaysia) Berhad. This system is developed to measure the job performance of Sunchirin Industry's employees who are in operator position. The measurements are based on the employee's knowledge, productivity, discipline and attendance. The user of this system is Sunchirin's supervisor, person who is responding in the employee assessment. The interviewing is conducted with the user to ensure that this system is meeting the user requirement. This system gives a lot of benefits to the company because this system enables the company to assess the work performance and contribution of the employee for the period of the assessment and enable the company to evaluate the employee's strong and weak points and thus discover his/ her potential for development in the company. Besides that, this system also makes the supervisor and workers in Human Resource Department job become easier, faster and efficient.